Humoral and cell-mediated response against SARS-CoV-2 variants elicited by mRNA vaccine BNT162b2 in healthcare workers: a longitudinal observational study. (February 2022) - Cassaniti, Irene; Bergami, Federica; Percivalle, Elena; Gabanti, Elisa; Sammartino, Josè Camilla; Ferrari, Alessandro; Adzasehoun, Kodjo Messan Guy; Zavaglio, Federica; Zelini, Paola; Comolli, Giuditta; Sarasini, Antonella; Piralla, Antonio; et al.
Abstract: Objectives: To assess the humoral and cell-mediated response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) elicited by the mRNA BNT162b2 vaccine in SARS-CoV-2-experienced and -naive subjects against a reference strain and SARS-CoV-2 variants. Methods: The humoral response (including neutralizing antibodies) and T-cell-mediated response elicited by BNT162b2 vaccine in 145 healthcare workers (both naive and positive for previous SARS-CoV-2 infection) were evaluated. In a subset of subjects, the effect of SARS-CoV-2 variants on antibody level and cell-mediated response was also investigated. Results: Overall, 125/127 naive subjects (98.4%) developed both neutralizing antibodies and specific T cells after the second dose of vaccine. Moreover, the antibody and T-cell responses were effective against viral variants since SARS-CoV-2 NT Abs were still detectable in 55/68 (80.9%) and 25/29 (86.2%) naive subjects when sera were challenged against β and δ variants, respectively. T-cell response was less affected, with no significant difference in the frequency of responders (p 0.369). Of note, two doses of vaccine were able to elicit sustained neutralizing antibody activity against all the SARS-CoV-2 variants tested in SARS-CoV-2-experienced subjects. Conclusions: BNT162b2 vaccine elicited a sustained humoral and cell-mediated response in immunocompetent subjects after two-dose administration of the vaccine, and the response seemed to be less affected by SARS-CoV-2 variants, the only exceptions being the β and δ variants. Increased immunogenicity, also against SARS-CoV-2 variant strains, was observed in SARS-CoV-2-experienced subjects. These results suggest that triple exposure to SARS-CoV-2 antigens might be proposed as valuable strategy for vaccination campaigns.